Sage extract and ascorbic acid derivative inhibit melanogenesis via downregulating keratinocyte-derived GM-CSF - Hirokazu Kubo; Mariko Moriyama; Saya Goto; Yuko Miyake; Maki Nakamura; Yuki Ozeki; Yukio Nakamura; Hiroyuki Moriyama (PLoS ONE, 2025)
Salvia officinalis (sage) extract has demonstrated potential as a functional ingredient for skin care application. However, its effect and mechanism in regulating skin pigmentation remain largely unclear. This study investigated the effects of sage ethanol extract (SGE) on melanogenesis and its underlying molecular mechanisms. Treatment with SGE in a human skin equivalent model (3D-skin) suppressed melanin production. To clarify the mechanism of action, the study focused on senescence-associated secretory phenotype (SASP) factors, which are implicated in age-related pigmentation changes. q-PCR and ELISA analyses showed that SGE inhibits melanogenesis by suppressing the expression of granulocyte-macrophage colony-stimulating factor (GM-CSF), a known SASP factor in keratinocytes. Interestingly, a similar effect was observed with L-ascorbic acid 2-glucoside (AG), previously identified as a tyrosinase inhibitor. Importantly, p38 and JNK MAP-kinase were identified as upstream regulators of GM-CSF that are suppressed by SGE. These findings provide new insights into how SGE and AG regulate pigmentation via keratinocyte-derived GM-CSF, highlighting their potential in modulating skin tone and pigmentation through cellular signaling pathways.